Estructura genética poblacional y conectividad del tiburón martillo (Sphyrna lewini) en áreas de crianza del Pacífico Tropical Oriental: Implicaciones para el manejo y la conservación - Elizondo Sancho, Mariana (2021)
Defining demographically independent units and understanding gene flow between them is essential for managing and conserving exploited populations. The scalloped hammerhead shark, Sphyrna lewini, is a coastal semi-oceanic species found worldwide in tropical and subtropical waters. Pregnant females give birth in shallow coastal estuarine habitats that serve as nursery grounds for neonates and small juveniles, and adults move offshore and become highly migratory. We evaluated the population structure and connectivity of S. lewini in coastal areas across the Eastern Tropical Pacific Ocean (ETP) using both nuclearencoded microsatellite loci and sequences of the mitochondrial DNA control region (mtCR). The mtCR defined two genetically discrete geographic groups: the Mexican Pacific and the central-southern Eastern Tropical Pacific (Guatemala, Costa Rica, Panamá, and Colombia). Overall, low levels of the mtCR were found; haplotype diversity ranged from 0.000 to 0.608, while nucleotide diversity ranged from 0.000 to 0.0015. More finegrade population structure analysis was suggested using microsatellite loci where Guatemala, Costa Rica, and Panamá differed significantly. Genetic diversity analysis with nuclear markers revealed an observed heterozygosity ranging from 0.68 to 0.71 and an allelic richness from 5.89 to 7.00. Relatedness analysis revealed that individuals within nursery areas were more closely related than expected by chance, suggesting that S. lewini may exhibit reproductive philopatric behaviour within the ETP. Findings of at least two different management units, and evidence of philopatric behaviour call for intensive conservation actions for this critically endangered species in the ETP.